A clinico-epidemiological profile, coinfections and outcome of patients with Influenza Like Illnesses (ILI) presenting to the emergency department during the COVID-19 pandemic - Darpanarayan Hazra; Gina Maryann Chandy; Abirahmi Thanjavurkar; Karthik Gunasekaran; Ankita Chowdary Nekkanti; Rathijit Pal; Mahesh Moorthy; Kundavaram Paul Prabhakar Abhilash (Journal of Family Medicine and Primary Care)
Background: During the COVID-19 pandemic, many patients presented to the emergency department (ED) with features of Influenza-like illnesses (ILI) and with other atypical presentations. This study was done to determine the etiology, co-infections, and clinical profile of patients with ILI. Methods: This prospective observational study included all patients presenting to the ED with fever and/or cough, breathing difficulty, sore throat, myalgia, gastrointestinal complaints (abdominal pain/vomiting/diarrhea), loss of taste and altered sensorium or asymptomatic patients who resided in or travelled from containment zones, or those who had contact with COVID-19 positive patients during the first wave of the pandemic between April and August 2020. Respiratory virus screening was done on a subset of COVID-19 patients to determine co-infection. Results: During the study period, we recruited 1462 patients with ILI and 857 patients with the non-ILI presentation of confirmed COVID-19 infection. The mean age group of our patient population was 51.4 (SD: 14.9) years with a male predominance (n-1593; 68.7%). The average duration of symptoms was 4.1 (SD: 2.9) days. A sub-analysis to determine an alternate viral etiology was done in 293 (16.4%) ILI patients, where 54 (19.4%) patients had COVID 19 and co-infection with other viruses, of which Adenovirus (n-39; 14.0%) was the most common. The most common symptoms in the ILI-COVID-19 positive group (other than fever and/or cough and/or breathing difficulty) were loss of taste (n-385; 26.3%) and diarrhea (n- 123; 8.4%). Respiratory rate (27.5 (SD: 8.1)/minute: p-value < 0.001) and oxygen saturation (92.1% (SD: 11.2) on room air; p-value < 0.001) in the ILI group were statistically significant. Age more than 60 years (adjusted odds ratio (OR): 4.826 (3.348-6.956); p-value: <0.001), sequential organ function assessment score more than or equal to four (adjusted OR: 5.619 (3.526-8.957); p-value: <0.001), and WHO critical severity score (Adjusted OR: 13.812 (9.656-19.756); p-value: <0.001) were independent predictors of mortality. Conclusion: COVID-19 patients were more likely to present with ILI than atypical features. Co-infection with Adenovirus was most common. Age more than 60 years, SOFA score more than or equal to four and WHO critical severity score were independent predictors of mortality.